Is night‐time surgical procedure for renal graft at higher risk than during the day? A single center study cohort of 179 patients. Issue 2 (18th November 2021) - Treacy, Patrick Julien; Barthe, Flora; Bentellis, Imad; Falagario, Ugo Giovanni; Prudhomme, Thomas; Imbert de La Phalecque, Laetitia; Shaikh, Aysha; Albano, Laetitia; Chevallier, Daniel; Durand, Matthieu
Abstract: Introduction: Various surgical centers tend to postpone a kidney transplantation (KT) to the following morning than to operate at night‐time. The objective of our study was to assess whether there was any difference between daytime and night‐time renal transplantation in our institution. Method: This study is a retrospective monocentric study including all the KTs that were performed between 2012 and 2013 by transplant expert surgeons in our institution. Clavien‐Dindo (CD) complications were classified according to 7 variables going from 1 to 5. Time before postgraft diuresis and delayed graft function (DGF) were also analyzed. Two groups of patients were formed according to threshold value of incision time (6.30 p.m.). Data comparison were performed using the Kruskal–Wallis nonparametric test. Results: A total of 179 patients were included. Median follow‐up was 24 months. Cold ischemia time was longer in the night‐time transplantation (1082 vs. 807 min, p < .001), but rewarming time was shorter (47.24 vs. 52.15 min, p = .628). No statistically significant differences were observed between the two groups using the Kruskal–Wallis method for CD complications (Qobs: 0.076; p = .735). CD complications proportion was similar, with a majority of grade II complications (72.7% daytime group vs. 75.4% night‐time group ( p = .735). DGF (19 patients for daytime group vs. 13 patients for night‐time group, p = .359) and time before postgraft diuresis (4.65 days daytime group vs. 5.27 days night‐time group, p = .422) were similar between both groups. Multivariate analysis did not show significant predictors of CD complications Grade 3 and more. Conclusion: Night‐time renal transplantation did not induce more postoperative CD complications than diurnal procedures in our cohort, challenging the false preconceptions that allow surgical teams to delay this surgery. Graphical abstract: